2022
DOI: 10.1186/s12913-022-07768-y
|View full text |Cite
|
Sign up to set email alerts
|

The development and psychometric evaluation of COVID-19 staff questionnaire for infectious disease outbreak readiness and preparedness (SQIDORP)

Abstract: Background The COVID-19 pandemic has inundated the capacity of hospitals across the globe, exhausting resources, and placing extreme burden on health care workers (HCWs). Hospital preparedness during infectious disease outbreak involves development and implementation of appropriate strategies, procedures, and adequate training for HCWs. Reliable and valid tools to evaluate the perception of HCWs on the effectiveness of hospital preparedness strategies are imperative and literature is yet to fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The Staff Questionnaire for Infectious Disease Outbreak Readiness & Preparedness (SQIDORP). The SQIDORP was adapted from Jokwiro et al [23] to assess nurses' preparedness to infectious diseases outbreak and composed of 19 items: these items were distributed into 4 categories, including perceived training (3 items), hospital administrative support (4 items), nurses' preparedness to monkeypox outbreak (9 items) and perceived support (3 items). A 3-point Likert scale was used ranged from (1 = not agree to 3 = agree).…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Staff Questionnaire for Infectious Disease Outbreak Readiness & Preparedness (SQIDORP). The SQIDORP was adapted from Jokwiro et al [23] to assess nurses' preparedness to infectious diseases outbreak and composed of 19 items: these items were distributed into 4 categories, including perceived training (3 items), hospital administrative support (4 items), nurses' preparedness to monkeypox outbreak (9 items) and perceived support (3 items). A 3-point Likert scale was used ranged from (1 = not agree to 3 = agree).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…A 3-point Likert scale was used ranged from (1 = not agree to 3 = agree). Scores ranged from 19 to 57 with high scores indicating a satisfactory level of preparedness and categorized as follow: satisfactory level of preparedness 39-57, and unsatisfactory level of preparedness [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The Generalized Anxiety Disorder Scale-7 (GAD-7). The GAD-7 was developed by Spitzer et al [24].…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Specifically, the compliance with protective health measures is often influenced by the population's knowledge, attitude, and practice (KAP) (16,17). For example, studies conducted during the severe acute respiratory syndrome (SARS) outbreak in 2003 in China and the US found that population attitudes and practices toward the SARS virus prevention were influenced by negatively held emotions and assumptions (18)(19)(20). Moreover, COVID-19 knowledge gaps have been associated with multiple socio-economic patterns (e.g, limited education, and low income)-and individuals who demonstrated both were found to undermined the risk of COVID-19 spread and symptoms (20).…”
Section: Introductionmentioning
confidence: 99%